(untitled) (Research, Society and Development, 2021)
Objective: to report the experience of Centro Universitário Christus regarding changes in the application of the Objective Structured Clinical Examination (OSCE) during COVID-19 pandemic. Methodology: experience report of faculty representatives. Results: During the emergency remote teaching (ERT) in COVID-19 pandemic, the assessment processes of the Knowledge, Skills and Attitudes module were adapted to Web-OSCE type assessments, performed synchronously, with students in their homes, using Google Meet®. The stations lasted for 5 minutes. On application day, students were confined to a Google Meet® room for initial orientation. Immediately afterwards, they were divided into virtual rooms with a room supervisor, and they were instructed to keep the camera and microphone connected. The standardized patient (PP) were actors, who were responsible for recording the station and presenting the command to the student on the screen and in the chat. After the student performed the task, the PP ended the recording, and the student left the room. The previously prepared feedback was made available in a short video at the end of the season. The assessment of the students stations performance was carried out by analyzing the recorded videos and filling out a checklist, asynchronously. Conclusion: The Web-OSCE proved to be a feasible method and it has potential for use in other scenarios, including assessment of teleconsultations. This method can be considered complementary and, together with other remote multiple-choice assessments, can estimate the cognitive gain of students during the ERT.